Geochemical and radiogenic isotope (Sr-Nd) characteristics of Paleoproterozoic anorthositic and granitoid rocks in the Umiakoviarusek Lake region, Labrador, Canada. - Piercey, Stephen J; Wilton, Derek HC (Canadian Journal of Earth Sciences, 1999)
Recent work in the north-central Labrador has identified Paleoproterozoic anorthositic and granitoid rocks that are spatially associated with, yet temporally distinct from, younger Mesoproterozoic intrusions of the Nain Plutonic Suite. The Umiakoviarusek Lake (UL) region of Labrador contains several of these Paleoproterozoic intrusions and provides an opportunity to study their geochemical and radiogenic isotope (Sr-Nd) characteristics. Geochemically, the anorthositic and granitoid rocks have features consistent with contemporary anorthositic and granitoid rocks from other anorthosite-mangerite-charnockite-granite complexes. The anorthositic rocks contain elevated contents of Al 2 O 3 , CaO, Sr, and Eu with low Ba, Rb, K, Zr, total rare earth elements (REE), and light REE. The granitoid rocks, on the other hand, contain lower concentrations of these elements along with elevated SiO 2 and K 2 O. Isotopic data at 2050 Ma for the anorthositic rocks (I Sr = 0.7048-0.7082; εNd = -4.1 to -15.9) and granitoid rocks (I Sr = 0.7036-0.7094, εNd = -5.1 to -9.7) are consistent with variable crustal and mantle contributions to their genesis. The relatively unradiogenic Sr and slightly evolved Nd isotopic data from the UL granitoid rocks is consistent with a significant juvenile mantle component, possibly derived from an underplating mantle plume; this component may also be present in the anorthositic rocks. The Nd and Sr isotopic data are also consistent with crustal contamination from Archean source materials; however, based on the existing isotopic database for the Nain Province gneisses, it is not possible to delineate a specific gneiss component. Furthermore, it is also quite possible that an Archean source, unlike any described at present, was a crustal source component in the UL intrusive rocks.